2008
DOI: 10.1103/physrevb.77.174305
|View full text |Cite
|
Sign up to set email alerts
|

Density matrix renormalization group approach to the spin-boson model

Abstract: We propose a density matrix renormalization group approach to tackle a two-state system coupled to a bosonic bath with continuous spectrum. In this approach, the optimized phonon scheme is applied to several hundred phonon modes that are linearly divided among the spectra. Although density matrix renormalization group cannot resolve very small energy scales, the delocalized-localized transition points of the two-state system are extracted by the extrapolation of the flow diagram results. The phase diagram is c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…Indeed, the standard one-bath spin-boson model (SBM1), obtained for α y = h y = 0, exhibits an interesting and much-studied [1][2][3][4][5][6][7] quantum phase transition (QPT) from a delocalized to a localized phase, with σ x = 0 or = 0, respectively, as α x is increased past a critical coupling α x,c . According to statisticalmechanics arguments, this transition is in the same universality class as the thermal phase transition of the one-dimensional (1D) Ising model with 1/r 1+s interactions.…”
mentioning
confidence: 99%
“…Indeed, the standard one-bath spin-boson model (SBM1), obtained for α y = h y = 0, exhibits an interesting and much-studied [1][2][3][4][5][6][7] quantum phase transition (QPT) from a delocalized to a localized phase, with σ x = 0 or = 0, respectively, as α x is increased past a critical coupling α x,c . According to statisticalmechanics arguments, this transition is in the same universality class as the thermal phase transition of the one-dimensional (1D) Ising model with 1/r 1+s interactions.…”
mentioning
confidence: 99%
“…17 In the sub-Ohmic case, all the variational calculations predicted a discontinuous transition, 18,19 but nonperturbative numerical calculations, such as numerical renormalization group ͑NRG͒ and densitymatrix renormalization group ͑DMRG͒, found a continuous transition instead. [22][23][24] The situation in the case of T 0 is also confusing. Variational calculations predicted a discontinuous transition at T 0 even in the super-Ohmic case, 25 a result which is in confliction with the known conclusion that the crossover only happens in the Ohmic and sub-Ohmic cases.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the incorrect employment of the state as the ground state [22], the main reason for obtaining the QPT in previous literatures [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] is the unreasonable treatment of the infrared divergence existing in the spectral functions for Ohmic and sub-Ohmic dissipations, which induced the degeneracy of the ground states in the low frequency domain. To clarify this point, we demonstrate below the potential infrared divergence in the treatments using the bath mode with continuous and discretized spectra, respectively.…”
mentioning
confidence: 99%
“…In contrast, for large α, the dissipation leads to a localization of the particle in one of the two σ z eigenstates, implying a doubly degenerate ground state. On the other hand, intensive studies have recently been paid on the sub-Ohmic dissipation, which also demonstrated the QPT between localized and delocalized phases [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In particular, the QPT could also happen in the absence of the local field (ǫ = 0) [7][8][9] from a non-degenerate ground state with zero magnetization below a critical coupling to a twofold-degenerate ground state with finite magnetization for a coupling larger than the critical value.…”
mentioning
confidence: 99%
See 1 more Smart Citation